Valery Podoroga’s Theory of Mimesis: the Sensory Aspects of Text Perception - Juodeika, Rytis (Problemos, 2022)
The paper aims to analyse and understand tensions and meanings in the notion of mimesis in the perspective of philosophical anthropology. Classical mimesis theories, which stretch from classical antiquity to modern works by E. Auerbach or P. Ricoeur, are often associated with poetics, narratology or other literature theory studies. V. Podoroga talks about anthropological and phenomenological mimesis, not only about ‘external’, Aristotelian version, but also about internal mimesis. He focuses on the experience of the body as the basis of mimesis. The author explains how mimesis in Podoroga’s version acquires new meanings and demonstrates how Podoroga’s matrixes of anthropograms complement, discuss and transgress hermeneutical models of Ricoeur.The author claims that the method of Podoroga brings us to some kind of a unique ‘system’, that could be compared to the ideas of ‘the death of the author’ (R. Barthes) or ‘the open work’ (U. Eco). Podoroga shows us an alternative, non-semiotic and mimetic approach in contemporary thought, that has not been widely discussed yet in both Russian and English sources.
Keywords: Podoroga; Ricoeur; mimesis; analytic anthropology; anthropograms